Monthly expenditure category fluctuations and trade-off in South Africa bottom of the pyramid households - Lappeman, James (School of Management Studies, 2017)
This exploratory study investigated changes in the allocation of household expenditure between various product or service categories in a sample of South African low-income or 'bottom of the pyramid' (BoP) households. First, the mixed methods research quantified the monthly income and expenditure fluctuations in the sample of households over a period of four months. In addition, study identified and quantified expenditure category trade-offs in the target households. Finally, a qualitative inquiry explained the reasons for the fluctuations and the trade-offs identified in the first two components. The study was based on the existing BoP proposition and specifically focused on BoP consumer decision-making theory. Methodologically, the study was a monthly longitudinal panel over four months. The quantitative component employed a once-off baseline questionnaire to gather household data. The participating households then completed monthly self-complete financial diary questionnaires that recorded both income and expenditure. The qualitative component involved interviews with representatives from the participating households and provided details to explain the underlying causes for changes in monthly expenditure patterns. The study was conducted in four provinces with eighty BoP households participating in the research. The study found significant variation in both household income and expenditure between months. The variation and consequent trade-offs between expenditure categories was caused by calendar-related phenomena (such as the festive season), income shocks, unforeseen expenses and spreading the household budget over multiple months. In addition, large fluctuations in income resulted in a constantly shifting allocation of expenditure to categories that required the most attention at a particular point in time. Informal savings (stokvels) and micro-enterprise expenses also contributed to fluctuations in income and expenditure. This study provides unique insights that fill a vacuum in the current body of academic and industry knowledge for this segment of close to forty million BoP South Africans. No study of this nature has been published in either South African or international journals.